Congenital Cytomegalovirus and Hearing Loss: A Pilot Cross-Sectional Survey of Otologists' and Pediatric Otolaryngologists' Knowledge. Issue 2 (May 2019) - Dedhia, Kavita; Tomlinson, Jennifer; Murray, Nancy; Park, Albert
Objective: To evaluate pediatric otolaryngologists, neurotologists, and otologists on awareness and knowledge of congenital cytomegalovirus (cCMV). Study Design: Pilot cross-sectional online survey. Setting: Otolaryngology practices. Subjects and Methods: An electronic multiple-choice questionnaire was sent email listserv to physician members of the American Society of Pediatric Otolaryngology and American Otological Society. The survey assessed demographics, physician awareness, and practice patterns. Data were collected and analyzed. Results: Seventy (14.5%) pediatric otolaryngologists and otologists responded. All responded that they are familiar with cCMV. Most were familiar with symptoms associated with cCMV with the exception of petechia/purpura. Less than 50% knew the incidence/natural history of cCMV-induced hearing loss. Only 63% knew that saliva or urine polymerase chain reaction/culture should be performed prior to 3 weeks of age. Less than half knew the indications for dry blood spot testing, and many incorrectly recommended serologic saliva or urine testing in a child >3 weeks old. Most respondents do not offer any diagnostic testing for cCMV or referral for antiviral therapy for those who may benefit from this treatment. Most either did not know the cCMV screening policy or did not have one at their institution. Conclusion: Despite a relatively low overall response rate, this study suggests several knowledge gaps and underutilization of cCMV testing by physicians who frequently encounter pediatric hearing loss. The findings from this pilot study demonstrate the need for further educational directives focused on cCMV to improve knowledge and incorporation of cCMV best practices.